THE COD LIVER OIL INSIGHTS: FROM FOLKLORE TO FACTS - Ahmad, Sharique; Anwar, Subuhi; Pratap, Pushpendra. D. (International Journal of Research -GRANTHAALAYAH, 2025)
This review article provides a concise overview of the background history, important nutritional components, evidence-based benefits, common misconceptions, probable risks, and future directions with regard to cod liver oil (CLO). It emphasizes the inclusion of recent studies to demystify known facts vs. common misconceptions, thus providing an insightful overview of the dynamic function of CLO as a food supplement. The article emphasizes CLO's proven effectiveness in lipid regulation, anti-inflammatory activity, and bone health promotion, and briefly touches on important safety concerns like vitamin A toxicity and drug interactions. It also discusses emerging therapeutic uses, providing a comprehensive, evidence-based review for healthcare professionals, researchers, and health practitioners.